2021
DOI: 10.3897/herpetozoa.34.e62007
|View full text |Cite
|
Sign up to set email alerts
|

Females of the four-eyed frog, Pleurodema thaul (Anura, Leptodactylidae), respond behaviourally to conspecific male scent

Abstract: Among amphibians, conspecific chemical communication has been widely studied in Caudata. Adult anurans, by contrast, have received less attention. Recently, it was shown that chemical scents are also relevant for adult anuran intraspecific communication. In this context, we evaluate whether females of the four-eyed frog (Pleurodema thaul) respond to conspecific male scents. We carried out a double choice experiment in a Y-maze. Females were repeatedly presented with the scents of several males versus distilled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
1
1
0
Order By: Relevance
“…Byrne and Keogh (2007) reported that chemical cues of male Australian toadlets (Pseudophryne bibronii) helped females in close-range mate location and might increase the efficacy of message transfer when combined with acoustic signals, which improved the ability of females to find nest site. Similar findings have been reported in studies with other terrestrial or aquatic anurans (Pearl et al 2000;Graham et al 2020;Rojas et al 2021). In contrast, females did not show a preference for undisturbed male odors in the present study, suggesting that the presence of undisturbed male odors may not facilitate mate detection or enhance sexual attractiveness in K. odontotarsus.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Byrne and Keogh (2007) reported that chemical cues of male Australian toadlets (Pseudophryne bibronii) helped females in close-range mate location and might increase the efficacy of message transfer when combined with acoustic signals, which improved the ability of females to find nest site. Similar findings have been reported in studies with other terrestrial or aquatic anurans (Pearl et al 2000;Graham et al 2020;Rojas et al 2021). In contrast, females did not show a preference for undisturbed male odors in the present study, suggesting that the presence of undisturbed male odors may not facilitate mate detection or enhance sexual attractiveness in K. odontotarsus.…”
Section: Discussionsupporting
confidence: 90%
“…Nevertheless, the role of chemical signals and cues in anuran mate choice has long been overlooked (Woodley 2015). Recently, a few studies have shown that females spend more time investigating male's chemical cues compared with control treatments (Graham et al 2020;Rojas et al 2021). However, how male chemical cues influence mate choice decisions based on acoustic signal design remains to be tested (Gong et al 2020).…”
Section: Introductionmentioning
confidence: 99%